Inhibition of Hydrogen Evolution in Aluminium-phosphate Refractory Binders - Bednárek, Jan; Ptáček, Petr; Švec, Jiří; Šoukal, František; Pařízek, Ladislav (Elsevier, 2016)
The study deals with the possibilities of inhibition of the reaction of aluminium-phosphate binders with iron scale, which is contained in bauxite. This material is mixed with phosphate binders to form refractories. The hydrogen is produced by this reaction causing the mixture foaming. The amount of evolved hydrogen was observed by the measuring by the Jank's calcimeter. Also the shape of oxidation-reduction potential of the binders was measured before and after mixing with aggregate using potentiometer. The influence of the addition of various cations on the hydrogen evolution and on the oxidation-reduction potential was observed. The effectiveness of the inhibitors was studied also visually by forming test elements.

The study deals with the possibilities of inhibition of the reaction of aluminium-phosphate binders with iron scale, which is contained in bauxite. This material is mixed with phosphate binders to form refractories. The hydrogen is produced by this reaction causing the mixture foaming. The amount of evolved hydrogen was observed by the measuring by the Jank's calcimeter. Also the shape of oxidation-reduction potential of the binders was measured before and after mixing with aggregate using potentiometer. The influence of the addition of various cations on the hydrogen evolution and on the oxidation-reduction potential was observed. The effectiveness of the inhibitors was studied also visually by forming test elements.
Inhibition of Hydrogen Evolution in Aluminium-phosphate Refractory Binders
Keywords: Phosphate binder; bauxite; refractories; wear iron; inhibition; calcimeter; potentiometer; Phosphate binder; bauxite; refractories; wear iron; inhibition; calcimeter; potentiometer